Programmable Photoelectric Memristor Gates for In Situ Image Compression. (21st September 2020) - Berco, Dan; Ang, Diing Shenp; Kalaga, Pranav Sairam
Abstract : Optoelectronic Memristors In article number 2000079, Dan Berco, Diing Shenp Ang, and Pranav Sairam Kalaga demonstrate the design principles for an in‐situ image compression circuit. Photoelectric memristor gates are utilized as building blocks much like logic gates in programmable gate‐arrays. Configured into a crossbar, they allow direct image imprint as well as performing fuzzy‐logic computations immediately upon acquisition.